HELP ME PLEASE I BEG U1!!!!!
HELP ME PLEASE I BEG U1!!!!! - 2

Answers

Answer 1
Answer: the first one is 41, since it occurs most frequently in the data
second one is 5.6, since it is in the middle of the data
working on others.....
Answer 2
Answer: The answer of the first question is 41 because the majority of the number in the list is 41 and there are three of them.

The answer of the second question is 3.4 which is in middle part in the list.

Related Questions

I want to know this problemas please
grant starteda marathon at 8:00 A.M. he took 4 hours 49 minutes to complete the marathon. when did he crosd the finish line
Which of the following are solutions to the equation below? Check all that apply.(3x + 4)2 = 14A. x= - √14/3 -4B. x= - √10/3c. x= √14-4/3d. x=√10/3e. x= - √14-4/3f. x= √14/3-4
What is the approximate volume of a sphere with a radius of 9 in.? Use 3.14 to approximate pi and express your answer in hundredths.
Simplify 5 - 2x -3 +x a) 2-x b) 1 C) x-2 d) 2-2x

Simplify the expression. (8x + 14) + (9x - 5)

Answers

use the associative property that says
a+(b+c)=(a+b)+c
and the commutative property that says
a+b=b+a
use together and get
(8x+14)+(9x-5)=8x+9x+14-5
add like terms
8+9=17
therefor
17x+14-5
14-5=9
17x+9 is the simpliefid form

1/6% of 295 help ASAP

Answers

Answer: 0.49

Step-by-step explanation:

1/6% X 295 = 0.00167 X 295

= 0.492~0.49

What does 805 tens equal

Answers

805 tens equals 8,050
your answer is 8,050

Consider the function represented by the equation x – y = 3. What is the equation written in function notation, with x as the independent variable?

Answers

We have an equation and we want to rewrite it as a function. The function will be: y = f(x) = -3 + x

So we start with the equation:

x - y = 3

And we want to write this in the form y = f(x) (because we want x to be the independent variable)

To do this, we just need to isolate y on one side of the equation.

x - y = 3

Now we subtract x in both sides:

x - y - x = 3 - x

-y = 3 - x

Now we multiply both sides by -1:

-1*(-y) = -1*(3 - x)

y = -3 + x

Then we have:

y = f(x) = -3 + x

This is the equation written in function notation.

If you want to learn more, you can read:

brainly.com/question/3139036

When the question asks to write the equation "in function notation, with x as the independent variable?", it simply is asking for the isolation of y. This means that y must be on its own side of the = sign with everything else on the other, because the dependent variable is being affected by the independent variable (hence the name "dependent").

The first step is to subtract x from both sides, so you end up with -y=3-x. This may look finished, but y is still attached to a negative sign. To fix this, we must divide both sides by -1 to receive our final answer of y=-3+x, which, when rearranged to be written in proper notation, reads as:

y=x-3

Hope I could help! :)

What is 32 divided by 5.98

Answers

5.351 is the answer or 5.3117056856 is the non rounded answer 
5.341, hope this helps you!

Simplify the expressions:

3x-1/3x+1

Answers